ROOTING OF ARATICUM-DE-PORCO STEM CUTTINGS WITH PLANT GROWTH REGULATORS - PINTO, Lausanne Soraya; ZUFFELLATO-RIBAS, Katia Christina; CARPANEZZI, Antonio Aparecido; TAVARES, Fernando Rodrigues; KOEHLER, Henrique Soares (Scientia Agraria, 2003)
Rollinia rugulosa Schl. (Annonaceae) is a native tree species suitable for ecosystem rehabilitation. This species produces edible fruits, that attract the local fauna. However, it presents a low rate of seed germination. To investigate the asexual reproduction, stem cuttings from native plants were collected in Colombo, State of Paraná, in the four seasons, beggining in march/2000. The following treatments with indolebutyric acid (IBA) and naphtaleneacetic acid (NAA) were used: 2000 mg.L-1 IBA, 4000 mg.L-1 IBA, 6000 mg.L-1 IBA, 2000 mg.L-1 NAA, 4000 mg.L-1 NAA, 6000 mg.L-1 NAA, 2000 mg.L-1 IBA + 2000 mg.L-1 NAA, and 5000 mg.L-1 NAA (Raizon 05â) in powder and the control (water). Cuttings collected during the fall and winter did not develop roots. Treatments using 6000 mg.L- 1 IBA and 2000 mg.L-1 IBA + 2000 mg.L-1 NAA showed the best results, during the spring, with 4% of root formation, for both treatments. Rollinia rugulosa showed a very low rate of rooting during the seasons for the tested conditions.